IMPROVEMENT IN ERADICATION OF HELICOBACTER PYLORI INFECTION WITH ADDITION OF LACTOBACILLUS REUTERI---A RANDOMIZED CONTROLLED TRIAL - Prof. Lubna Kamani; Dr. Mehreen Akmal; Dr. Adeel Rahat; Dr. Sajjad Jameel; Leticia Moreira MD, Phd; Javier P. Gisbert MD, PhD (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction & Objective: The eradication rate of Helicobacter pylori (HP) has decreased with different treatment regimens over the time. This study was conducted to compare the eradication rate of HP infection and improvement of symptoms treated by sequential therapy (ST) with addition of Lactobacillus Reuteri (LR) versus ST only.Material and Methods: This open label randomized control trial was conducted in Department of Gastroenterology, Liaquat National Hospital, Karachi, from July 2020 to June 2021.A Total of 195 treatment naïve patients were included in each group. Patients of group A received ST and LR and patients of group B received ST only.Total duration of treatment was two weeks in both groups. Patients of both groups were also evaluated for severity of abdominal symptoms and its betterment after treatment according to the Gastrointestinal Symptom Rating Scale (GSRS) at first visit and on follow up visit after 4weeks. Four weeks after the treatment, HP eradication test was performed by stool antigen test (SAT) or urea breath test (UBT).Results: A total of 390 patients were enrolled in the study and both groups consisted 195 patients each. HP eradication was successful in 116(84.7%) in group A and 94(85.5%) in Group B (p=0.864) patients when SAT was the method of post eradication test while using UBT as post eradication test 49(84.5%) in Group A and 80(94.1%) in Group B (p=0.057) patients showed successful eradication. The symptom improvement assessed by using GSRS showed higher rates of symptom betterment in Group A 175(89.7%) as compared to Group B 53(27.2%) respectively (p=0.001).Conclusion: This study showed that addition of LR to ST showed no increment in rates of HP eradication. However, there was an increase in effectiveness in terms of improvement of symptoms compared to the ST alone.Trial registration: The study is registered with clinical trials.gov with first trial registered on 27/01/2023 with the registration number# NCT05701683.